New calculation model and application research on weak water-flushed zones distribution prediction in radial flow well patterns of heterogeneous oil reservoirs. - Mengyun Li; Guicai Zhang; Haihua Pei; Ping Jiang; Liu Yang (PLoS ONE)
After prolonged waterflooding development, the main integrated oil reservoirs in the X Oilfield have largely entered the late stage of waterflooding, with an average water cut reaching approximately 98%. However, a significant amount of remaining oil still accumulates in the weak water-flushed zones of low-permeability layers, which presents substantial development potential. Therefore, accurately predicting the distribution of weak water-flushed zones is crucial for optimizing extraction measures and enhancing recovery rates. However, during the development process, especially in the ultra-high water cut stage, the continuous changes in oil-water flow resistance in multi-layer heterogeneous reservoirs make it very difficult to accurately predict the distribution of weak water-flushed zones. At present, the prediction of weak water-flushed zone is highly dependent on complex physical models, the computational process is cumbersome, and the relevant research on the distribution of weak water-flushed zone under radial flow is scarce. To address this, based on Darcy's Law and Buckley-Leverett's non-piston water flooding theory, taking the flow resistance coefficient as the index, this paper deduces the water drive front advancement equation for different permeability layers under radial flow conditions in heterogeneous reservoirs (including barriers). This study established an iterative calculation method for the advancement distance of the water drive front in low-permeability layers, forming a simple and convenient method for describing the distribution of weak water-flushed zones in heterogeneous reservoirs. On this basis, the accuracy of the proposed weak water-flushed zone prediction method is verified through numerical simulation experiments based on the geological model of the X oil field. The results show that the relative error between the calculated results of new calculation model and numerical simulation results is less than 5%, indicating that the method is simple to use and highly accurate. Finally, using the established prediction method, we calculated the limiting conditions for the existence of weak water-flushed zones in the X oil field test area. Under the oil field's model conditions, when the permeability ratio exceeds 2.4, weak water-flushed zones exist in the low-permeability layers when the water cut reaches 98%. Furthermore, the initiation limit of the weak water-flushed zone is clarified: under the model conditions (with a permeability ratio of 10), the weak water-flushed zone in the low-permeability layers can be initiated when the permeability ratio decreases to 2.4 after plugging adjustments or the viscosity of the injected displacing medium reaches 10 mPa·s. This prediction method can provide technical guidance for optimizing decision-making in the efficient development of ultra-high water cut oil fields.